Risk habitat megacity - Krellenberg, Kerstin; Hansjürgens, Bernd; Martínez, Francisco; Heinrichs, Dirk (Springer Berlin Heidelberg, 2012)
Megacity development and the inherent risks and opportunities for humans and the environment is a theme of growing urgency in the 21st century. Focusing on Latin America where urbanization is most advanced, this book studies the complexity of a 'mega-urban system' and explores interrelations between sectors and issues by providing an in-depths study of one particular city, Santiago de Chile. The book attempts to (i) focus on the emergence of risk in megacities by analyzing risk elements, (ii) evaluate the extent and severity of risks, (iii) develop strategies to cope with adverse risks, and (iv) to guide urban development by combining concepts with empirical evidence. Drawing on the work of an interdisciplinary and international consortium of academic and professional partners, the book is written for scholars in cross-cutting areas of urban, sustainability, hazard, governance and planning research as well as practitioners from local, regional and international organizations.